2022
DOI: 10.3390/nano12172966
|View full text |Cite|
|
Sign up to set email alerts
|

Nematicidal Potential of Green Silver Nanoparticles Synthesized Using Aqueous Root Extract of Glycyrrhiza glabra

Abstract: Meloidogyne incognita (root-knot nematode) is a devastating soil-borne pathogen which can infect almost all cultivated plants around the globe, expediting huge pecuniary losses. The purpose of current study was to use the aqueous root extract of Glycyrrhiza glabra for synthesizing silver nanoparticles (GRAgNPs) and assess their nematicidal potential against M. incognita by in vitro methods, including hatching inhibition and mortality assays. The active uptake of FITC labeled GRAgNPs by the nematode and their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…The concentration of FS-Ag-NPs needed to kill the J2s was found to be higher in our study, as other studies have reported the use of higher concentrations ranging from 20 to 150 ppm [ 48 , 49 ] and 125–1000 mg/L [ 50 ]. Our findings are not in agreement with previous reports by Baronia et al [ 51 ], who achieved 100% mortality at a concentration of 2 ppm after 24 h of Ag-NPs treatment, and Rani et al [ 11 ], who observed complete death of Meloidogyne incognita J2s at a low dose of 6 ppm after 12 h of treatment with Glycyrrhiza glabra -silver nanoparticles synthesized.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The concentration of FS-Ag-NPs needed to kill the J2s was found to be higher in our study, as other studies have reported the use of higher concentrations ranging from 20 to 150 ppm [ 48 , 49 ] and 125–1000 mg/L [ 50 ]. Our findings are not in agreement with previous reports by Baronia et al [ 51 ], who achieved 100% mortality at a concentration of 2 ppm after 24 h of Ag-NPs treatment, and Rani et al [ 11 ], who observed complete death of Meloidogyne incognita J2s at a low dose of 6 ppm after 12 h of treatment with Glycyrrhiza glabra -silver nanoparticles synthesized.…”
Section: Resultscontrasting
confidence: 99%
“…Nowadays, it is routinely stressed that agricultural output must be increased to keep up with the nutritional needs of the expanding global population. To this end, nanotechnology shows significant promise in many areas of agriculture, including the control of pests, pathogens, weeds, and diseases; the protection of plants; the preservation of soil and water quality; the monitoring of pollution; the improvement of crop quality; and the creation of nano-sensors [ 11 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of aqueous flower extract of Musa acuminate -based AgNPs, IC 50 of 55ppm was reported against Vero cells [ 47 ]. AgNPs exhibited cytotoxicity via interaction with functional groups of cellular proteins, entering the cells by endocytosis, followed by their retention by P-glycoproteins [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although our synthesized AgNPs demonstrated varied toxicity towards P. brachyurus, they did not have any negative effects on soybean plants. In a broader context, different studies suggest that exposure for up to 3 days at 100–800 µmol L −1 is needed to achieve noticeable reductions in phytonematode mobility or mortality [ 55 , 56 , 57 ]. In our experiments, it was observed that a 48 h exposure with AgNPs was required to neutralize over 50% of the nematode population’s mobility (IC50) at concentrations ranging from 3.66 to 25.18 µmol L −1 .…”
Section: Discussionmentioning
confidence: 99%